Compreendendo o lugar a partir das percepções e experiências dos moradores da cidade de São Rafael/RN - Souza, Patrícia Maraísa de (Universidade Federal Rural do Semi-Árido, 2019)
This research on understanding the place of the old and new São Rafael / RN aims to understand the place from the perception and experiences of the residents, identifying the changes that occurred with the relocation of the city, taking into account the socioeconomic and cultural aspects, through construction of the Armando Ribeiro Gonçalves Engineer Dam in the 1980s, making it possible to understand the different views on the Geographic Space of the old and the new São Rafael. The study is characterized by a research of a qualitative and methodological nature: bibliographic, documentary and field research. Theoretically, it was based on scholars such as Tuan (1980), Holzer (1998), Santos (2006), Bosi (1987), Callai (2013) and others. As results we emphasize that the study of the place is relevant, since from it we can know and interpret the reality, be it rural or urban, reflecting the context and the changes that have occurred over time, as we perceive in the case of this research aspects from the old to the new city in the face of globalization, identifying the importance of pedagogical practices linked to the teaching of Geography in Field Education. In view of the research, it was possible to observe that such a process of displacement was not intended for the residents of São Rafael, where it was characterized as a forced process leaving ruptures and continuities
Monografia
Keywords: Percepção; Lugar; São Rafael; Ensino de geografia; Educação do campo; Perception; Place; São Rafael; Teaching geography; Field education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL